2020
DOI: 10.3855/jidc.13160
|View full text |Cite
|
Sign up to set email alerts
|

Perception and practice of social distancing among Egyptians in COVID-19 pandemic

Abstract: Introduction: Social distancing is principally intended to reduce infectious disease transmission by decreasing interactions among people in a broader community. Keeping social distancing is an essential public health measure to resist the COVID-19 pandemic. Methodology: a cross sectional study was conducted among 1,036 Egyptians using an online questionnaire between 5 and 10 May 2020. Results: There was significant association between the practice of social distancing and some sociodemographic fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 8 publications
3
11
0
Order By: Relevance
“…However, they are more likely to use the social distancing strategy compared to females. These findings are in line with a study on the practice of social distancing done in the Egyptian context [46]; being male and working and living in urban communities positively contribute to the practice of social distancing, with high statistical significance. In addition, our study indicates that household income and race also are contributing factors to the practice of social distancing.…”
Section: Preventive Behavioursupporting
confidence: 89%
“…However, they are more likely to use the social distancing strategy compared to females. These findings are in line with a study on the practice of social distancing done in the Egyptian context [46]; being male and working and living in urban communities positively contribute to the practice of social distancing, with high statistical significance. In addition, our study indicates that household income and race also are contributing factors to the practice of social distancing.…”
Section: Preventive Behavioursupporting
confidence: 89%
“…However, lack of conveyance and difficulty in staying away from friends was more significantly observed in interns and residents rather than in attending physicians. The study from general population of Egypt also observed that staying away from friends and family was the most important barrier to efficiently practicing social distancing [8].…”
Section: Discussionmentioning
confidence: 92%
“…There have been international and local studies to judge the knowledge, attitudes, and practices about Covid-19 on both the general population [14][15][16][17][18] as well as the HCWs [19][20][21][22]. However only one study has been done which focuses solely on social distancing and assesses perceptions and practices of the general population [8]. The study reported that males with age>30 and those with higher levels of education tend to have significantly better social distancing practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In recent history the preventive measures were applied to control the spread of swine and bird flu. 9,10 The best method to prevent SARS-CoV-2 infection is the practicing of physical distancing, 11 which refers to the maintenance of a safe distance between people who are not from one home. 12 Social distancing includes the practice of staying at home and compliance with at least 1-metre space.…”
Section: Introductionmentioning
confidence: 99%